Demographic, Clinical, Laboratory and Radiological Spectrum of COVID-19 patients - Abdul Rabb Bhutto, Amanullah Abbasi, Khalil Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find out the demographic, clinical, laboratory and radiological spectrum of COVID-19 patients. Study design: Cross-sectional observational study. Place and duration of study: Al-Tibri Medical College Hospital, Isra University Karachi campus Karachi from June 2021 to December 2021. Methodology: The study enrolled adult patients of both genders with COVID-19 infection confirmed through positive qualitative RT‑PCR from nasal swab. After obtaining informed consent each confirmed patient with COVID-19 disease underwent a process of detailed medical history, clinical examination, laboratory tests, and radiological assessment. Based on presentation patients were divided into three groups; Group I, asymptomatic patients having only positive for COVID 19 were advised for self-isolation at home, Group 2 patients with mild symptoms and admitted to ward for observation and monitoring, while Group 3 were patients with moderate to severe disease and requiring intensive care. Results: A total of 179 patients with a mean age of 49.218±13.237 years (rang 18 to 85 years) were enrolled in the study with gender based presentation 51 (28.5%) were women and 128 (71.5%) were men. Clinically; main symptoms were fever in 155 (86.6%), shortness of breath 129(72.1%), cough 126 (70.39%), and body ache in 104 (58.1%). Twenty six (14.5%) patients were asymptomatic (Group I), 107(59.8%) were symptomatic mild disease (Group II) and 37 (20.7%) patients presented with moderate to severe symptomatic illness (Group III). The majority of study participants 140 (78.21%) have various comorbidities, DM 60(33.5%), hypertension in 61(34.1%). Conclusion: Our study has highlighted the variability of most aspects of COVID-19 and this might be the main reason why the spectrum of the disease cannot be predicted. Radiologic, pulmonary with clinical patterns are relatively specific but extra pulmonary involvement especially hepatic may misguide and worse the prognosis. Keywords: COVID-19. Pandemic. Demographic. Clinical. Laboratory. Radiologic. Spectrum.